Mechanical ventilation as a surrogate for diagnosing the onset of abdominal compartment syndrome (ACS) in severely burned patients (TIRIFIC-study Part II) - Boehm, Dorothee; Arras, Denise; Schröder, Christina; Siemers, Frank; Corterier, C. C.; Lehnhardt, Marcus; Dadras, Mehran; Hartmann, Bernd; Kuepper, Simon; Czaja, Kay-Uwe; Kneser, Ulrich; Hirche, Christoph (Burns, 2020)
Intra-abdominal compartment syndrome (ACS) is a devastating complication in burn patients with a high mortality. Apart from high-volume resuscitation as known risk factor, also mechanical ventilation seems to influence the development of ACS. The TIRIFIC trial is a retrospective, matched-pair analysis. Thirty-eight burn patients with ACS were matched for burned total body surface area (TBSA), age and mechanical ventilation (MV). In contrast to the already published part I addressing fluid resuscitation as a risk factor, the parameters analyzed in part II were maximum and average PEEP and peak pressure levels as well as serum lactate levels and prokinetic therapy. For subgroup-analysis the ACS-group was split up into an early-onset and late-onset ACS-group according to the median time between burn trauma and ACS. The groups were analyzed with a two-sided Mann-Whitney-U-test with significance set at p < 0.05. In the ACS-group all ventilation pressures (maximum and average PEEP and peak pressure levels) were significantly increased compared to control. The subgroup-analysis showed significantly increased maximum PEEP and peak pressure levels in early- and late-onset ACS-groups versus control. However, the average ventilation pressure levels were only increased in the early-onset ACS-group (average PEEP p = 0.0069; average peak pressure p = 0.05). The TIRIFIC trial showed significantly increased ventilation pressures in the ACS group in general as a surrogate parameter to support early diagnostics. Especially, maximum PEEP levels and peak pressures are significantly increased in both, early- and late-onset ACS. As an addition to the actual WSACS guidelines we suggest IAP measurement in mechanically ventilated burn patients if ventilating pressures are rising continuously without a clear pulmonary or otherwise identifiable reason. (C) 2020 Elsevier Ltd and ISBI. All rights reserved.
Gesehen am 26.11.2020